Les nouvelles formes de l’agir politique en perspective, France-Espagne - Serge Buj (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish legislative elections of June 26 and December 20, 2015, as well as the French presidential election of May 2017, lead to a certain number of questions around the political phenomena that have been developing for several years in Spain and France or, more broadly, in constituted states whose sovereignty is based on so-called « universal » suffrage and the exercise of power on delegation democracy, parliamentary democracy. These phenomena are most often classified as NMS (new social movements) insofar as they reject in their discourse the party-form, both in terms of structure (centralized, hierarchical) and functioning, particularly in decision-making that goes beyond the local level. Are they one manifestation among others of a movement of crisis and renovation of the political party system or are they symptomatic of a period of great global ideological reclassification? These are the questions that arise when observing and assessing local situations. Using the two examples of France and Spain, we will attempt to develop an obviously fragmentary reflection on the nature and discourse of these NMS, including the question of whether treating them as such is not to be too hasty.